Exploring the impact of equipment modifications on novice tennis players: a scoping review - Piquer-Piquer, Ana; Crespo, Miguel; Ramón-Llin, Jesús; Guzmán, José Francisco; Martínez-Gallego, Rafael (Frontiers in Psychology, 2025)
Tennis equipment modifications, such as smaller rackets and low-compression balls, are increasingly being used because they can better align with beginners’ physical capabilities, enhancing learning and engagement. This scoping review aimed to map current research on equipment modifications for beginner tennis players, identifying how these modifications impact skill acquisition, game performance, biomechanical variables, psychological aspects, and coaches’ perspectives. Searches across the Web of Science, Scopus, PubMed, and SPORTDiscus, along with expert input following the PRISMA procedures, yielded 35 studies. These studies involved empirical interventions related to scaled tennis equipment for beginners and were published in English or Spanish. Narrative reviews and studies lacking empirical data were excluded. The results indicate that equipment modifications enhance control, technique, and engagement in skill acquisition, improve tactical play with more aggressive strokes, and reduce joint stress, thereby minimizing injury risk. Psychological benefits include greater enjoyment and self-efficacy, and coaches strongly support these adaptations. These findings suggest practical implications for junior tennis development. However, future research should focus on expanding real-game applications, increasing participant diversity, and conducting detailed psychological and biomechanical assessments to further optimize player progression.